2022
DOI: 10.1128/msystems.01342-21
|View full text |Cite|
|
Sign up to set email alerts
|

Reduced Virulence and Enhanced Host Adaption during Antibiotics Therapy: a Story of a Within-Host Carbapenem-Resistant Klebsiella pneumoniae Sequence Type 11 Evolution in a Patient with a Serious Scrotal Abscess

Abstract: Carbapenem-resistant Klebsiella pneumoniae (CRKP) has disseminated worldwide and can cause life-threatening infections, including pneumonia, bloodstream infections, urinary tract infections, intraabdominal infection, liver abscess, and meningitis. CRKP infection is the leading cause of high mortality in hospitals.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Further analyses, including gene knockout and phenotypic tests, indicated that the ntrd morphotype was caused by capsule deficiency mediated by point mutations, or disruption of the cps genes by diverse ISs (include ISKpn74 and ISKpn26). A recent study by Ye et al also indicated that deletion of the acyltransferase gene ( act ) from the cps locus plays a crucial role in the evolution of virulence of ST11 CRKP [ 38 ]. The capsule is a critical virulence factor, and was shown to be costly in nutrient-rich media in a study by Buffet et al [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further analyses, including gene knockout and phenotypic tests, indicated that the ntrd morphotype was caused by capsule deficiency mediated by point mutations, or disruption of the cps genes by diverse ISs (include ISKpn74 and ISKpn26). A recent study by Ye et al also indicated that deletion of the acyltransferase gene ( act ) from the cps locus plays a crucial role in the evolution of virulence of ST11 CRKP [ 38 ]. The capsule is a critical virulence factor, and was shown to be costly in nutrient-rich media in a study by Buffet et al [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such microdiversity is a result of either repetitive infections or in vivo diversifying evolution of a single clone during prolonged infections, and it could be clinically important when different strains have different AMR susceptibilities. For example, ST11-KPC-2 isolates have been reported to gain additional resistance to ceftazidime-avibactam and tigecycline by mutations in D179Y and the ramR gene during long-term treatments ( 20 , 38 ). Here, we compared genomic sequences of 19 sets of CRKPs that were each isolated from the same patients.…”
Section: Discussionmentioning
confidence: 99%
“…One of the potential reasons for this may be stated as increased AMR and prolonged antimicrobial exposure, which come with a fitness cost to bacteria such as reduced virulence and altered pathogenesis [38,39]. In previously published studies, it has been observed that A. baumannii has diminished its biofilm formation ability, in vivo dissemination, and surface motility upon conferring colistin resistance [40,41].…”
Section: Discussionmentioning
confidence: 99%